Chronic toxicological effects of β‐diketone antibiotics on Zebrafish (Danio rerio) using transcriptome profiling of deep sequencing. Issue 11 (6th April 2015) - Wang, Huili; Yin, Xiaohan; Li, Fanghui; Dahlgren, Randy A.; Zhang, Yuna; Zhang, Hongqin; Wang, Xuedong
ABSTRACT: Transcriptome analysis is important for interpreting the functional elements of the genome and revealing the molecular constituents of cells and tissues. Herein, differentially transcribed genes were identified by deep sequencing after zebrafish ( Danio rerio ) were exposed to β‐diketone antibiotics (DKAs); 23, 129 and 23, 550 mapped genes were detected in control and treatment groups, a total of 3238 genes were differentially expressed between control and treatment groups. Of these genes, 328 genes (213 up‐ and 115 down‐regulation) had significant differential expression ( p < 0.05) and an expression ratio (control/treatment) of >2 or <0.5. Additionally, we performed Gene Ontology (GO) category and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses, and found 266 genes in the treatment group with annotation terms linked to the GO category. A total of 77 differentially expressed transcriptional genes were associated with 132 predicted KEGG metabolic pathways. Serious liver tissue damage was reflected and consistent with the differences in genetic classification and function from the transcriptome analysis. These results enhance our understanding of zebrafish developmental processes under exposure to DKA stress. © 2015 Wiley Periodicals, Inc. Environ Toxicol 31: 1357–1371, 2016.